2018
DOI: 10.1001/jama.2018.3708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atropine With Propofol vs Atropine With Atracurium and Sufentanil on Oxygen Desaturation in Neonates Requiring Nonemergency Intubation

Abstract: ClinicalTrials.gov Identifier: NCT01490580, EudraCT number: 2009-014885-25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 42 publications
2
71
0
Order By: Relevance
“…Because of its rapid onset and recovery, and its ease of use, propofol as a sedative for endotracheal intubation has been implemented into clinical practice in several neonatal intensive care units (NICUs) 13–17. Previous trials studying propofol have shown conflicting results on sedative effect and concerning effects on blood pressure 16–19…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its rapid onset and recovery, and its ease of use, propofol as a sedative for endotracheal intubation has been implemented into clinical practice in several neonatal intensive care units (NICUs) 13–17. Previous trials studying propofol have shown conflicting results on sedative effect and concerning effects on blood pressure 16–19…”
Section: Introductionmentioning
confidence: 99%
“…Used propofol starting doses range from 1.0 to 2.5 mg/kg, with cumulative doses ranging from 1.0 to 6.0 mg/kg for successful intubation 15–19. Although gestational age (GA) and postnatal age (PNA) are important determinants of propofol pharmacokinetics,20 fixed propofol starting doses are often used for the entire neonatal population regardless of GA and PNA.…”
Section: Introductionmentioning
confidence: 99%
“…This trial will be the first multicenter, double blind, randomised, placebo controlled trial evaluating premedication before LISA with an expected number of participants of 542. In addition it will examine the neurodevelopmental outcome at 2 years of age of preterm infants who received a few doses of propofol or ketamine shortly after birth [22,44].…”
Section: Discussionmentioning
confidence: 99%
“…Mediali-pide® is used in the control group to ensure that the 2 arms are indistinguishable. Medialipides® is an emulsion of medium and long triglycerides based derived from soya oil and has the same appearance as propofol [20,22].…”
Section: Blindingmentioning
confidence: 99%
See 1 more Smart Citation